Authenticity and Values - Fran Silvestre (Oz, 2018)
In our case, it is not a matter of pri - oritizing our vision or of seeking authenticity in each of the projects. For us, dialogue is very important, which is always present, since the work becomes part of the identity of those who inhabit it. It is an unmistakable expression of your personality or your corporate culture. Likewise, in each project we look for continuity. Continuity with both the environ - ment that we must respect, as well as understood from a spatial and temporal point of view, valuing the architecture that is capable of go - ing through time without becoming obsolete.